2014
DOI: 10.1016/j.jpsychires.2014.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Intensive residential treatment for severe obsessive-compulsive disorder: Characterizing treatment course and predictors of response

Abstract: Background Intensive residential treatment (IRT) is effective for severe, treatment-resistant obsessive-compulsive disorder (OCD). We sought to characterize predictors and course of response to IRT. Methods Admission, monthly, and discharge data were collected on individuals receiving IRT. We examined the association between baseline characteristics and percent change in OCD symptoms as measured by the Yale-Brown Obsessive-Compulsive Scale (Y-BOCS) using linear regression. We compared baseline characteristic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 43 publications
1
31
0
Order By: Relevance
“…Given the possibility that cerebral Glu levels may be affected by nicotine use (Licata and Renshaw, 2010), we cannot rule out the potential confounding effects of nicotine use on our findings. Finally, the OCD patients included in this study were being treated in an intensive residential treatment program and thus likely represent a severe, treatment-refractory subgroup (Brennan et al, 2014). Therefore, our findings may not be reflective of the broader OCD population.…”
Section: Discussionmentioning
confidence: 93%
“…Given the possibility that cerebral Glu levels may be affected by nicotine use (Licata and Renshaw, 2010), we cannot rule out the potential confounding effects of nicotine use on our findings. Finally, the OCD patients included in this study were being treated in an intensive residential treatment program and thus likely represent a severe, treatment-refractory subgroup (Brennan et al, 2014). Therefore, our findings may not be reflective of the broader OCD population.…”
Section: Discussionmentioning
confidence: 93%
“…We identified 41 studies that met our screening criteria of treatment of OCD in either an inpatient, day-patient or residential unit setting. Of these, 22 were excluded for failing to meet one of the criteria: one because patients were from an outpatient service (Olatunji et al, 2013); three for not using the Y-BOCS as an outcome measure (Kwee, Duivenvoorden, Trijsburg, & Thiel, 1986;Ruppert, Zaudig, Hauke, Thora, & Reinecker, 2001; Van den Hout, Emmelkamp, Kraaykamp, & Griez, 1988); four because they used the Y-BOCS self-report version (Cole Monaghan et al, 2015;Grøtte et al, 2015;Simpson et al, 2013), two because they were adolescent services (Arai, Ichikawa, Ejiri, & Watanabe, 2006;Bjorgvinsson et al, 2008); two because they reported on treatment outcomes for an eating disorders service, with only some patients having comorbid OCD (Cumella, Kally, & Wall, 2007;Olatunji, Tart, Shewmaker, Wall, & Smits, 2010); one for having a sample size of two patients (Carmin & Wiegartz, 2000); or nine patients (Drummond, Pillay, Kolb, & Rani, 2007); one for being a review rather than a research study (Winkelmann & Hohagen, 1995); two because they did not include CBT as part of the treatment (Haghighi et al, 2013;Shafti & Kaviani, 2015); one for not including data on post-treatment Y-BOCS scores (Brennan et al, 2014); and one as it was unpublished (Alosso, 2012).…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
“…In addition, we wanted to investigate predictors of treatment outcome and dropout rates during treatment (see Table 2). Therefore, 10 of the studies included in the meta-analysis which also included analysis of predictors of treatment outcome and dropout were combined with three studies that were excluded from the meta-analysis as they included only predictors of treatment outcome (Brennan et al, 2014;Stewart et al, 2009Stewart et al, , 2006.…”
Section: Study Selectionmentioning
confidence: 99%
“…Given the possibility that cerebral GSH levels may be impacted by nicotine use (82), we cannot exclude a potential confounding effect of nicotine use on our findings. Finally, our OCD patients were recruited from an intensive residential treatment program, and thus likely represented a severe, treatment-refractory subgroup (83), potentially not representative of the broader OCD population.…”
Section: Discussionmentioning
confidence: 99%